Short and long term follow-up of laparoscopic resection for colorectal cancer NCI experience - Haytham Waheed Yousry Gareer; Ashraf Saad Zagloul; Medhat Khafagi; Mohamed Hany Elnaggar (Cairo : Haytham Waheed Yousry Gareer, 2009)
This study included 119 patients presented with colorectal cancer and treated by laparoscopic resection between January 2000 and December 2005.116 patients were treated aiming at curative resection and 3 patients had palliative resection.The study included 54 males and 62 females followed up for a minimum of 36 month
Thesis (M.Sc.) - Cairo University - National Cancer Institute - Department of Oncology (Surgical)
Issued also as CD
Keywords: Colorectal surgery; Long term follow-up; Short - term follow-up